Recent Advances in the Structure-Based and Ligand-Based Design of IKKβ Inhibitors as Anti-inflammation and Anti-cancer Agents - Huang, Jing-Jie; Chu, Hong-Xi; Jiang, Zheng-Yu; Zhang, Xiao-Jin; Sun, Hao-Peng; You, Qi-Dong (Current Medicinal Chemistry, 2014)
NF-ΚB is a significant transcription factor that regulates the expression of various pro-survival genes. IKK is a crucial protein kinase that activates NF-ΚB translocating from cytoplasm to nucleus for DNA binding. It is composed of three subunits, IKKα, IKKβ, IKKγ (NEMO), where IKKα and IKKβ are catalytic subunits, and IKKγ is the regulatory subunit. Many diseases, such as Hodgkin’s disease, Hepatitis-associated hepatocellular carcinoma, colorectal cancer, prostate cancer, rheumatoid arthritis and inflammatory bowel disease, are related to IKK and NF-ΚB. So far, various IKK inhibitors targeting the ATP binding site have been identified through high throughput screening, rational design or in silico methods, however, only three of them (CHS-828, EB-1627 and IMD-1041) have been under clinical studies, indicating the strategy for the design of IKK inhibitors need to be reinspected. Besides ATP-competitive inhibitors, several other inhibitors have also been disclosed recently, which provide novel concepts to the discovery of IKK inhibitors. In this review, we focus on two parts: 1) the chemotypes and binding patterns of the traditional ATP-competitive IKK inhibitors; 2) novel strategies for the identification of non-ATP-competitive IKK inhibitors as NF-ΚB modulators. Through these discussions we hope to present inspirations for the development of new IKK inhibitors.
Keywords: NF-ΚB